2013
DOI: 10.3233/bmr-2012-0343
|View full text |Cite
|
Sign up to set email alerts
|

Work related neck pain in Iranian dentists: An epidemiological study

Abstract: Results indicated that the prevalence of neck pain in dentists appears to be high. Therefore, further studies on different preventive strategies in dentists' population seem necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
3
20
1
Order By: Relevance
“…These results were consistent to the results of the previous epidemiological studies 16,17. Many studies have showed that dentists reported more pain in their neck and shoulders 18. Lower back was the second site of musculoskeletal disorder.…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent to the results of the previous epidemiological studies 16,17. Many studies have showed that dentists reported more pain in their neck and shoulders 18. Lower back was the second site of musculoskeletal disorder.…”
Section: Discussionsupporting
confidence: 92%
“…Prolonged static postures (PSPs) are often unavoidable in daily dental operations [4, 6]. Forward-head postures which involve holding the neck and head in an unbalanced forward position to gain better visibility during treatment are common among dentists [4, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged static postures (PSPs) are often unavoidable in daily dental operations [4, 6]. Forward-head postures which involve holding the neck and head in an unbalanced forward position to gain better visibility during treatment are common among dentists [4, 6]. Sustained contraction of the cervical muscles due to the PSPs may cause the weakening of spinal discs, which in turn increases the risk of disc degeneration of herniation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neck pain is a common complaint of people in contemporary society and causes disability and discomfort, lessens job efficiency, and increases the use of health care services . Of the different occupations, office workers, especially intensive computer users, are at high risk for developing neck disorders .…”
Section: Introductionmentioning
confidence: 99%